6r-2(2-r)=4(2r-1)

Simple and best practice solution for 6r-2(2-r)=4(2r-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6r-2(2-r)=4(2r-1) equation:


Simplifying
6r + -2(2 + -1r) = 4(2r + -1)
6r + (2 * -2 + -1r * -2) = 4(2r + -1)
6r + (-4 + 2r) = 4(2r + -1)

Reorder the terms:
-4 + 6r + 2r = 4(2r + -1)

Combine like terms: 6r + 2r = 8r
-4 + 8r = 4(2r + -1)

Reorder the terms:
-4 + 8r = 4(-1 + 2r)
-4 + 8r = (-1 * 4 + 2r * 4)
-4 + 8r = (-4 + 8r)

Add '4' to each side of the equation.
-4 + 4 + 8r = -4 + 4 + 8r

Combine like terms: -4 + 4 = 0
0 + 8r = -4 + 4 + 8r
8r = -4 + 4 + 8r

Combine like terms: -4 + 4 = 0
8r = 0 + 8r
8r = 8r

Add '-8r' to each side of the equation.
8r + -8r = 8r + -8r

Combine like terms: 8r + -8r = 0
0 = 8r + -8r

Combine like terms: 8r + -8r = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 2.5h=100-15 | | -13=x+5 | | 5x+38=13x-58 | | 2x^4+5x^2=3 | | -0.333x=15 | | 6x+56=11x+11 | | -3m=5(m-8) | | v^2+3v-40=0 | | .75y=6 | | v^2+7+6=0 | | 3z-9=5z-3z | | 100=15-2.5h | | 6m=-42 | | 6050=-10x^2+335x+3700 | | 25+5+12=132 | | -12s=-120 | | -9t=36 | | 3y=42 | | 25+5+12= | | 6x^4-36x^2=0 | | 15n=-30 | | 9x-4y=15 | | 2x^2-67x+730=0 | | 7-7x=107-35x | | (2r+5)(3r^2-16r+5)=0 | | 2x-y=3 | | 7x=91 | | 2(w-7)+10w=34 | | -52-10x=7x+16 | | 3x+7=-15-8x | | 2x+10= | | 4x-y=0 |

Equations solver categories